Three new combinations and one lectotypification of fern and lycophyte taxa from the French overseas territories - Rouhan, Germinal; Boullet, Vincent; Field, Ashley; Schuettpelz, Eric (Phytotaxa, 2021)
With the exception of French Guiana and Adélie Land, the French Overseas Territories (FOTs) are islands and their biodiversity is remarkable in many ways. Notably, they harbour numerous unique taxa leading to exceptionally high rates of endemism. Among French endemic plants, 95% occur in the FOTs, accounting for ca. 4000 species of tracheophytes and ‘bryophytes’ (Gargominy et al. 2020).